PHARMACOLOGIC TREATMENT OF THE IRRITABLE BOWEL SYNDROME: A COMPREHENSIVE SYSTEMATIC REVIEW - Sijabat, Landong; Novettiandari, Guinanti (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Abdominal pain and changes in stool frequency are two of the symptoms of Irritable Bowel Syndrome (IBS), a chronic gastrointestinal illness. As there is no known cure, treatment focuses on symptom management. Patients struggle with psychological and emotional issues that lower their quality of life. Clinical trials have demonstrated the therapeutic effects of several therapeutic drugs, which may improve GI symptoms and general quality of life. Effective treatment of IBS requires an understanding of the connection between pharmaceutical medicines and the illness. Methods: Following PRISMA 2020 guidelines, this systematic review concentrated on full-text English literature published between 2014 and 2024. Editorials and review articles that appeared in the same journal as the submission were not accepted without a DOI. The literature was assembled using a variety of online databases, including ScienceDirect, PubMed, and SagePub. Result: The study screened about 20.000 publications using reputable sources including Science Direct, SagePub, and PubMed. Seven papers were found to be pertinent for systematic investigation, after which the entire material was examined in more detail. Conclusion: IBS treatment has shown significant improvement in patients with Minesapride, a novel 5-HT4 receptor agonist, and tenapanor. Tenapanor showed significant improvement in symptoms, treatment metrics, and satisfaction, while geraniol improved the inflammatory profile. Melatonin showed improvement in IBS score and GI symptoms, but no significant improvement in frequency of defecations per week. Amitriptyline showed effectiveness over placebo, while co-micronized PEA/PD improved IBS symptoms in children.